AB0922 FDG-PET/CT Is A Valuable Tool for Relapsing Polychondritis. (15th July 2016) - Wakiya, R.; Ozaki, H.; Shimada, H.; Nakashima, S.; Takeuchi, Y.; Izumikawa, M.; Kameda, T.; Dobashi, H.
Abstract : Background: Relapsing polychondritis (RP) is a comparatively rare inflammatory disorder t in which recurrent episodes of inflammation occur in the external ear, nose, and joints. Although the pathogenesis of RP is unclear, it is believed to involve autoimmune mechanism such as autoantibody to type II collagen. Clinically, diagnosis in early stages of RP is difficult because of few typical physical findings. Furthermore, airway involvement is the most important complication of RP, and is associated with significant morbidity and mortality. Therefore it is important to diagnosis and treat RP in early stages. On the other hand, fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) has been an established in a field of oncology. Recently, FDG-PET/CT is used as diagnostic tool for inflammatory disorder such as infection or collagen vascular disease. Objectives: We investigate the features and the usefulness of FDG-PET/CT in the diagnosis of RP. Methods: We enrolled the five RP patients (M/F: 1/4) who fulfilled the RP criteria by Damiani and Levine, and treated in our facility between 2005 and 2015. All patients had undergone FDG-PET/CT before treatment. Inflammatory lesion was evaluated by using the maximum standardized uptake value (SUV max). Furthermore, we performed follow-up FDG-PET/CT due to evaluate the efficacy of treatment for RP. Results: FDG-PET/CT findings revealed abnormal FDG accumulation in the cartilages for all five patients. The lesions of abnormal FDG accumulation were tracheal/bronchial in 3 cases, auricular cartilage in 2 cases. The mean SUV max in tracheal/bronchial was 4.84 and in auricular cartilage was 2.53. All RP patients received glucocorticoid (GC) treatment. 3 patients were performed methylprednisolone-pulse therapy. All RP patients had well responce to initial GC treatment. However three patients were refractory for GC treatment. In these patients, one treated with methotrexate combined with GC and another 2 cases cyclophosphamide. The follow-up FDG-PET/CT was undergone in 2 patients. These findings revealed that FDG accumulation was significantly decreased or disappeared. Conclusions: In RP patients, FDG-PET/CT is useful for the early diagnosis. Additionally, we suggest that FDG-PET/CT is valuable for monitoring response to treatment. References: Jinlin Wang et al. Ann Nucl. Med. (2014)28:276–284 Yamashita H et al. Rheumatology 2014 Aug;53(8):1482–90 Disclosure of Interest: None declared